MENINGKATKAN KETERAMPILAN BERBAHASA MENGGUNAKAN MEDIA PEMBELAJARAN BERBASIS APLIKASI CANVA RA AISYIYAH 2 KOTA SERANG - Elis Mayasari (Jurnal Anak Bangsa, 2024)
The problem of this research is how to improve linguistic aspects using a learning environment based on the Canva application at RA Aisyiyah 2, Serang city. with this type of research, research that focuses on classroom situations or often called Classroom Action Research, which aims to improve the linguistic aspects of early childhood by using a Canva-based learning environment. RA Aisyiyah 2 Serang city application. RA Aisyiyah 2 group B's language skills have improved. Based on the data, it can be seen that in cycle I there were 22 children who met the initial development criteria of 100%. This is because there are still errors in each indicator so that in cycle I it was found that it was not yet at the level of success, whereas in cycle II the number of children who developed very well according to the criteria was 20 children. children. percentage of 80% and those included in the criteria for achieving according to expectations of 2 children 20% percentage for each indicator of language proficiency after activities with the Canva application-based learning environment. Thus, it can be said that this learning improves learning outcomes, namely achieving success or being included in the BSB (Very Well Developed) category